The Clairaut's theorem on rotational surfaces in pseudo-Euclidean 4-space with index 2 - Almaz, Fatma; Kulahci, Mihriban A. (Charles Univ, Fac Mathematics & Physics, 2024)
Clairaut's theorem is expressed on the surfaces of rotation in semi Euclidean 4-space. Moreover, the general equations of time-like geodesic curves are characterized according to the results of Clairaut's theorem on the hyperbolic surfaces of rotation and the elliptic surface of rotation, respectively.
Keywords: Clairaut's theorem; surfaces of rotation; pseudo-Euclidean 4-space; geodesic curve